Effect of protein and amino acids supplements on muscle strength and physical performance: a scoping review of randomized controlled trials - Al‐Rawhani, Alaa H.; Adznam, Siti Nur'Asyura; Abu Zaid, Zalina; Md. Yusop, Nor Baizura; M. Sallehuddin, Hakimah; Alshawsh, Mohammed A. (John Wiley and Sons, 2025)
Protein and amino acid supplementation is an effective intervention that significantly enhances physical function and reduces frailty and sarcopenia in older adults. This scoping review aims to map and synthesize the available evidence on the effects of various types of protein and amino acid supplementation in this population. Following the PRISMA-ScR guidelines, we conducted a literature search to identify clinical trials examining the effects of protein and amino acid supplementation, with or without physical exercise, on muscle strength, physical performance, and body composition in healthy, frail, or sarcopenic older adults. Our analysis of 80 trials with a total of 5290 participants examines the evidence for the effectiveness of protein supplementation in enhancing muscle strength and body composition. Whey protein, creatine, milk protein, leucine, essential amino acids, and soy protein were the most used types of protein, and our findings indicate that whey protein, creatine, and milk protein yield the best results when used in conjunction with resistance training. Additionally, leucine and milk protein have shown the potential to enhance body composition even without concurrent resistance training. In conclusion, studies on the effectiveness of whey protein in improving muscle strength and body composition in older adults with resistance training are inconsistent. More research is required to explore the potential benefits of soy and leucine-enriched supplements. Protein supplementation's impact on physical performance remains inconclusive. Further studies are needed to determine the effects of protein types and supplementation on muscle-related parameters in older adults.